A Three‐Component Synthesis of 3‐Functionally Substituted 5, 6‐Dihydropyrrolo[2, 1‐a]isoquinolines. Issue 1 (24th November 2021) - Miftyakhova, Almira R.; Borisova, Tatiana N.; Titov, Alexander A.; Sidakov, Matvey B.; Novikov, Roman A.; Efimov, Ilya V.; Varlamov, Alexey V.; Voskressensky, Leonid G.
Abstract: Synthesis of novel C3‐substituted 5, 6‐dihydropyrrolo[2, 1‐ a ]isoquinolines via a three‐component domino reaction of 1‐aroyl‐3, 4‐dihydroisoquinolines, terminal alkynes and CH‐acids under microwave irradiation in dry acetonitrile is described. The method developed enables the obtainment of highly functionalized compounds with pharmacophore groups, which are potentially biologically active. Abstract :